Impact of Oxidative Stress on Age-Associated Decline in Oocyte Developmental Competence - Sasaki, Hiroyuki; Hamatani, Toshio; Kamijo, Shintaro; Iwai, Maki; Kobanawa, Masato; Ogawa, Seiji; Miyado, Kenji; Tanaka, Mamoru (Frontiers in Endocrinology, 2019)
Reproductive capacity in women starts to decline beyond their mid-30s and pregnancies in older women result in higher rates of miscarriage with aneuploidy. Age-related decline in fertility is strongly attributed to ovarian aging, diminished ovarian reserves and decreased developmental competence of oocytes. In this review, we discuss the underlying mechanisms of age-related decline in oocyte quality, focusing on oxidative stress (OS) in oocytes. The primary cause is the accumulation of spontaneous damage to the mitochondria arising from increased reactive oxygen species (ROS) in oocytes, generated by the mitochondria themselves during daily biological metabolism. Mitochondrial dysfunction reduces ATP synthesis and influences the meiotic spindle assembly responsible for chromosomal segregation. Moreover, reproductively aged oocytes produce a decline in the fidelity of the protective mechanisms against ROS, namely the ROS-scavenging metabolism, repair of ROS-damaged DNA, and the proteasome and autophagy system for ROS-damaged proteins. Accordingly, increased ROS and increased vulnerability of oocytes to ROS lead to spindle instability, chromosomal abnormalities, telomere shortening, and reduced developmental competence of aged oocytes.